2021
DOI: 10.1038/s41598-021-92228-6
|View full text |Cite
|
Sign up to set email alerts
|

A step towards sustainable glass fiber reinforced concrete utilizing silica fume and waste coconut shell aggregate

Abstract: Today, it’s getting harder to find natural resources for concrete production. Utilization of the waste materials not just helps in getting them used in concrete, cement, and other construction materials, but also has various secondary advantages, for example, saving in energy, decrease in landfill cost, and protecting climate from pollution. Considering this in the development of modern structural design, utilizing waste materials instead of natural aggregate is a good option to make concrete that is sustainab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…The second objective of this study was to add GGBS into recycling coarse aggregate concrete to offset its porous nature by filling voids and by the pozzolanic reaction, which enhances the mechanical performance of recycled coarse aggregate concrete. Zaid et al showed that although pozzolanic materials improved the compressive strength of concrete, however, the concrete still had less tensile capacity, resulting in brittle failure that is unacceptable [4]. Further research was recommended in [4] where fibers must be added to GGBS recycled aggregate concrete to achieve high strength, durable, and ductile concrete.…”
Section: Research Significancementioning
confidence: 99%
See 4 more Smart Citations
“…The second objective of this study was to add GGBS into recycling coarse aggregate concrete to offset its porous nature by filling voids and by the pozzolanic reaction, which enhances the mechanical performance of recycled coarse aggregate concrete. Zaid et al showed that although pozzolanic materials improved the compressive strength of concrete, however, the concrete still had less tensile capacity, resulting in brittle failure that is unacceptable [4]. Further research was recommended in [4] where fibers must be added to GGBS recycled aggregate concrete to achieve high strength, durable, and ductile concrete.…”
Section: Research Significancementioning
confidence: 99%
“…Zaid et al showed that although pozzolanic materials improved the compressive strength of concrete, however, the concrete still had less tensile capacity, resulting in brittle failure that is unacceptable [4]. Further research was recommended in [4] where fibers must be added to GGBS recycled aggregate concrete to achieve high strength, durable, and ductile concrete. Therefore, the final objective of this study was to add steel fiber to GGBS recycled coarse aggregate concrete to obtain high-strength durable concrete.…”
Section: Research Significancementioning
confidence: 99%
See 3 more Smart Citations